Collaborative Governance in Waste Management (Case Study: Lahat Regency) - M. Harryasa Tafani; Azhar Azhar; Sena Putra Prabujaya (JURNAL ECONOMINA, 2026)
Solid waste management is a complex public issue that requires collaboration among multiple stakeholders. Lahat Regency continues to face challenges, including increasing waste generation, limited infrastructure, human resources, and financial capacity, as well as low community participation in waste segregation at the source. This study aims to analyze the implementation of collaborative governance in solid waste management in Lahat Regency using the Collaborative Governance Regime (CGR) framework developed by Emerson, Nabatchi, and Balogh (2012). This study employed a qualitative descriptive approach. Data were collected through interviews, observations, and document analysis involving the Environmental Agency of Lahat Regency, Harapan Waste Bank, DP Partner Main Waste Bank, and Anugerah Waste Collector. Data were analyzed through data condensation, data display, and conclusion drawing. The findings indicate that solid waste management in Lahat Regency involves the local government, waste banks, waste collectors, and the community in community-based waste reduction and management initiatives. From the CGR perspective, the system context, collaborative drivers, collaboration dynamics, and collaborative actions have been established through regulatory support, leadership, stakeholder engagement, and the implementation of capacity-building programs, public awareness campaigns, waste segregation, and waste utilization initiatives. These collaborative efforts have strengthened community-based waste management, enhanced the capacity of waste banks, and developed an economically valuable waste utilization chain. However, the effectiveness of collaboration remains constrained by limited resources, low community participation, and suboptimal coordination among stakeholders.